2012
DOI: 10.1007/s10646-012-0974-4
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Effects of imidacloprid, a neonicotinoid pesticide, on reproduction in worker bumble bees (Bombus terrestris)

Abstract: In the original publication of the article, the conversion of imidacloprid concentrations from lg L -1 into parts per billion (ppb) has been miscalculated in certain sections of the text. The authors would like to correct this error and provide the corrected conversions in the altered text below (correct ppb values given in italics).• …exposure to imidacloprid at an environmentally realistic level of 1 lg L -1 (=0.8 ppb)… • …oocytes were smaller in bees from microcolonies exposed to imidacloprid at 125 lg L -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…They recorded significantly reduced nest growth and an 85 % decrease in queen production in imidacloprid-exposed colonies compared to control colonies. This reduction in colony performance is likely due to a combination of factors such as reduced pollen input (as demonstrated by Gill et al 2012 and Feltham et al 2014 ) and perhaps impaired fecundity of queens (following Laycock et al 2012a , b ). In an 11 week greenhouse study, caged queenright colonies of B. impatiens were fed treatments of 0, 10, 20, 50 and 100 ppb of imidacloprid, respectively, and clothianidin in sugar syrup (50 %) (Scholer and Krischik 2014 ).…”
Section: Terrestrial Invertebratesmentioning
confidence: 95%
See 2 more Smart Citations
“…They recorded significantly reduced nest growth and an 85 % decrease in queen production in imidacloprid-exposed colonies compared to control colonies. This reduction in colony performance is likely due to a combination of factors such as reduced pollen input (as demonstrated by Gill et al 2012 and Feltham et al 2014 ) and perhaps impaired fecundity of queens (following Laycock et al 2012a , b ). In an 11 week greenhouse study, caged queenright colonies of B. impatiens were fed treatments of 0, 10, 20, 50 and 100 ppb of imidacloprid, respectively, and clothianidin in sugar syrup (50 %) (Scholer and Krischik 2014 ).…”
Section: Terrestrial Invertebratesmentioning
confidence: 95%
“…Neonicotinoids such as thiacloprid, thiamethoxam and imidacloprid decrease brood production, larval eclosion, colony growth rate and the number of queens reared in bumblebees (Tasei et al 2000 ; Mommaerts et al 2010 ; Whitehorn et al 2012 ). Studies suggest that the reduction in brood production may be associated with a reduction in pollen and sugar consumption by adult bees (Laycock et al 2012a , b ). The rearing of honeybees on brood comb containing high levels of pesticide residues results in delayed larval development and emergence and shortened adult longevity (Wu et al 2011 ).…”
Section: Terrestrial Invertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides are known to have strong effects on pollinators, particularly on wild bees (e.g. Brittain et al, 2010;Gill et al, 2012;Laycock et al, 2012) or in simplified landscapes such as those encountered in northern France (Park et al, 2015 The quality of the assessment of crop pollinator dependence may also influence the two indices. Here, we have used available data, which are coarse: the classes of pollinator dependence can span up to 30%.…”
Section: Two Independent Indices Show Consistent Patterns In the Pollmentioning
confidence: 99%
“…A healthy bumblebee or honeybee colony will grow and produce sexuals (gynes and males). Reproductive output is arguably the best measure of colony fitness [32,63,64] but other proxies such as colony growth or larval production are also useful fitness measures [64,65]. As described in §3a, laboratory experiments have demonstrated that flupyradifurone exposure can increase honeybee larval mortality [50,51] and can also reduce adult emergence [51], which could have knock-on effects on colony growth.…”
Section: (B) Bee Fitness and Reproductive Outputmentioning
confidence: 99%